KONSEP AKHLAK IMAM AL GHAZALI - Mohd Aji Isnaini (Fakultas Dakwah dan Komunikasi, Universitas Islam Negeri, Raden Fatah Palembang, 2011)
Surely I was sent to perfect morals, Rasulullahn hadith illustrates how important it is morality that must-have for the survival of God on earth, the definition of morality according to al-Ghazali was